2016
DOI: 10.4149/bll_2016_071
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of global ischemic/reperfusion and Tacrolimus administration on CA1 region of hippocampus: gene expression profiles of BAX and BCL2 genes

Abstract: BACKGROUND: It is well known that hippocampus has a pivotal role in learning, formation and consolidation of memory. Global cerebral ischemia causes severe damage to pyramidal neurons of the CA1 region and usually results in residual neurological defi cits following a recovery from ischemia. Scientists investigate to fi nd the molecular mechanism of apoptosis and to use this cell death for clinical treatment. OBJECTIVE: In this investigation, we evaluated the molecular mechanism of FK-506 in apoptosis using ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Therefore, the balance between apoptotic Bax proteins and anti-apoptotic Bcl-2 proteins determines activation and inhibition of the intrinsic apoptosis pathway. Consistent with the results of this study, previous studies that used different experimental models have reported tacrolimus-induced apoptosis was associated with a decrease in Bcl-2/Bax ratio and/or caspase-3 activation [16,35,43,44,45,46]. Moreover, several natural products with antioxidant properties have been shown to protect against tacrolimus-mediated cytotoxicity and tacrolimus-induced suppressions of Bcl-2/Bax ratio and/or caspase-3 activation [16,34,43,44], which are very similar to the results of this study.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the balance between apoptotic Bax proteins and anti-apoptotic Bcl-2 proteins determines activation and inhibition of the intrinsic apoptosis pathway. Consistent with the results of this study, previous studies that used different experimental models have reported tacrolimus-induced apoptosis was associated with a decrease in Bcl-2/Bax ratio and/or caspase-3 activation [16,35,43,44,45,46]. Moreover, several natural products with antioxidant properties have been shown to protect against tacrolimus-mediated cytotoxicity and tacrolimus-induced suppressions of Bcl-2/Bax ratio and/or caspase-3 activation [16,34,43,44], which are very similar to the results of this study.…”
Section: Discussionsupporting
confidence: 92%
“…The Bcl-2 family members (Bcl-2, Bcl-xL, Bax, Bak) are involved in the regulation of apoptotic signaling by mediating mitochondrial membrane permeability. Bcl-2 plays a vital role in the anti-apoptosis process by inhibiting Bax migration to the mitochondrial membrane or interfering with the Bak oligomerization process (26). The present results demonstrated that PAR2 deficiency attenuated cardiomyocyte apoptosis after H/R with decreased c-PARP and increased Bcl-2 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that tacrolimus alleviates I/R injury in various organs, including the ovary, liver and brain (16,17). It has also been revealed that tacrolimus may exert anti-oxidative and anti-apoptotic Association of the PPARγ/PI3K/Akt pathway with the cardioprotective effects of tacrolimus in myocardial ischemic/reperfusion injury effects (18,19). However, the effects of tacrolimus on MIRI and the exact mechanism are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%